Influence of cyclic frozen and defrost on mechanical properties of polytetrafluoroethylene (PTFE)-coated woven fabrics - Andrzej Ambroziak; Paweł Kłosowski (Archives of Civil Engineering, 2023)
This research aims to determine the influence of the cyclic process of freezing and defrosting on the mechanical properties of the chosen glass fibres and PTFE-coated woven fabrics. The specimens were subjected to freezing at about -20˚C for 4 h and thawing by full immersion into the water at about +20˚C for 4 h. The fabric samples after 25 and 50 frozen cycles were air-dried at room temperature for one week and then subjected to uniaxial tensile tests. The same tests have been performed on a reference group of specimens, which were not exposed to temperature change. The authors determined the tensile strength, and longitudinal stiffnesses resulting from performed tests. Although the investigated coated woven fabrics expressed a reduction in the tensile strength in water soaking conditions, the performed frozen cycles don’t show a significant decrease in strength under uniaxial tensile tests.